An Immunological Approach to Increase the Brain's Resilience to Insults. (24th April 2014) - Lin, En-Ju D.; Symes, C. Wymond; Townsend-Nicholson, Andrea; Klugmann, Matthias; Klugmann, Claudia B.; Lehnert, Klaus; Fong, Dahna; Young, Deborah; During, Matthew J.
Abstract : We have previously demonstrated the therapeutic potential of inducing a humoral response with autoantibodies to the N -methylD -aspartate (NMDA) receptor using a genetic approach. In this study, we generated three recombinant proteins to different functional domains of the NMDA receptor, which is implicated in mediating brain tolerance, specifically NR1[21–375], NR1[313–619], NR1[654–800], and an intracellular scaffolding protein, Homer1a, with a similar anatomical expression pattern. All peptides showed similar antigenicity and antibody titers following systemic vaccination, and all animals thrived. Two months following vaccination, rats were administered the potent neurotoxin, kainic acid. NR1[21–375] animals showed an antiepileptic phenotype but no neuroprotection. Remarkably, despite ineffective antiepileptic activity, 6 of 7 seizing NR1[654–800] rats showed absolutely no injury with only minimal changes in the remaining animal, whereas the majority of persistently seizing rats in the other groups showed moderate to severe hippocampal injury. CREB, BDNF, and HSP70, proteins associated with preconditioning, were selectively upregulated in the hippocampus of NR1[654–800] animals, consistent with the observed neuroprotective phenotype. These results identify NR1 epitopes important in conferring anticonvulsive and neuroprotective effects and support the concept of an immunological strategy to induce a chronic state of tolerance in the brain.